2013
DOI: 10.1680/stbu.10.00060
|View full text |Cite
|
Sign up to set email alerts
|

Shear strengthening of reinforced concrete continuous beams

Abstract: This paper presents the results of an experimental investigation to evaluate the contribution of carbon-fibrereinforced polymer sheets in enhancing the shear strength of continuous reinforced concrete beams. A total of five, two-span concrete continuous beams with rectangular cross-section were tested. One beam without strengthening was used as the control and the other four beams were strengthened with different arrangements of polymer sheets.The variables selected were various wrapping schemes and anchorage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…Table 3 shows that the shear resistance of RC beams can be improved by epoxy-bonded CFRP fabric strips as U-wrapped placed at 900 to the horizontal axis of the beam. These results are similar to those found by Ahmad et al [30], who concluded that CFRP material can be used to increase the shear performance. The results demonstrated that the CFRP fabric strips effectively improve the shear strength of RC beams, but the contribution shows variation dependent upon the bond surface area.…”
Section: Shear Strengthsupporting
confidence: 91%
See 1 more Smart Citation
“…Table 3 shows that the shear resistance of RC beams can be improved by epoxy-bonded CFRP fabric strips as U-wrapped placed at 900 to the horizontal axis of the beam. These results are similar to those found by Ahmad et al [30], who concluded that CFRP material can be used to increase the shear performance. The results demonstrated that the CFRP fabric strips effectively improve the shear strength of RC beams, but the contribution shows variation dependent upon the bond surface area.…”
Section: Shear Strengthsupporting
confidence: 91%
“…It is clear from Table 2 and Figure 4, that the mid-span deformations at failure for Beams FA-0, VR2A, VR2B, VR2C, VR2D, VR2E and VR2F were 4.1, 5.9, 6.3, 9.5, 6.7, 7.5 and 8.6 mm respectively, while the ductility indexes were 1.05, 1.56, 1.9, 2.6, 2.08, 2.2 and 2.5 respectively. Figure 4 shows that beam FA-0 is initially stiffer than all the CFRP fabric U-wrapped strengthened Beams (VR2A, VR2B, VR2C, VR2D, VR2E and VR2F), which is similar to the work of Ahmad et al, [30].…”
Section: Load-deflection Behavioursupporting
confidence: 81%